Stability determination of the formulations containing hyaluronic acid. (9th March 2015) - Olejnik, A.; Goscianska, J.; Zielinska, A.; Nowak, I.
Synopsis Objectives The aim of this work was to investigate the long‐term stability of four emulsions (creams and ointments) developed for carrying hyaluronic acid (HA) for dermal penetration. Methods The stability of obtained formulations was analysed by multiple light scattering and laser diffraction methods. Results The experimental results showed that the moisturizing creams were more stable than the ointments containing HA. The migration phenomenon of particles was observed in soft ointment with HA and the flocculation phenomenon was detected in ointment based on lanolin. The larger the water content, the more stable formulation can be, due to hygroscopic properties of HA. Conclusions The identification of instability phenomena was shortened dramatically using optical method such as multiple light scattering. Even small changes in the stability of emulsion were determined very early. We suggest that the moisturizing creams may be more suitable than ointments to carry HA for dermal absorption. These studies are a significant first step towards further exploration into what form of HA would assure maximum effect, give consumers satisfaction and guarantee safety during application.